2018
DOI: 10.4314/jfas.v9i6s.87
|View full text |Cite
|
Sign up to set email alerts
|

Theeffectivenessofginger compress on non-specific low back pain

Abstract: The purpose of this study was to identify the effectiveness of ginger compress in relief non-specific low back pain and reduce functional disability due to low back pain. After screening, 15 participants were randomly allocated into two groups: experimental group (n=8) received ginger compress treatment for 20 minutes per session, three sessions per week for a total of ten sessions and control group (n=7) did not received any treatment. Numeric Rating Scale for pain and OswetryDisability Questionnaire were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Zingiber officinale, commonly known as ginger, has a long tradition of medicinal use as an antiinflammatory agent for musculoskeletal diseases in Ayurvedic and Chinese medicine for more than 2500 years [12,33,34]. In Unani medicine dry ginger is listed as a medicine to treat cancer by Al-Razi [41,42].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zingiber officinale, commonly known as ginger, has a long tradition of medicinal use as an antiinflammatory agent for musculoskeletal diseases in Ayurvedic and Chinese medicine for more than 2500 years [12,33,34]. In Unani medicine dry ginger is listed as a medicine to treat cancer by Al-Razi [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Gingerols, shogaols, and zingerone are thought to play a role in nociception and pain processing [31]. A study conducted by Lem and Lee, (2017) showed that that ginger compress is effective in pain relief and reduces functional disability in patients with non-specific low back pain [33]. A Randomized, double blind clinical trial conducted by Rayati et al, (2017) concluded that ginger powder is as effective as ibuprofen in the management of postsurgical sequelae [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation